VAT Gap Dependence and Fiscal Administration Measures - Lešnik, Tomaž; Jagrič, Jagrič; Jagrič, Vita (Naše gospodarstvo/Our economy, 2018)
The paper examines the VAT gap estimated on the basis of VAT tax returns. The assessment of tax gap dependence is examined based on macroeconomic influences and the measures of the Slovenian fiscal administration. Regarding the latter, the number of audits being performed and the effects of audit activity (tax yield) have been considered. The results of the analysis support the thesis that the tax gap is reduced in conditions of economic growth. The fiscal administration measures showed the desired effect. An important factor lowering the gap was proven to be the number of (VAT) audits. A similar impact on the tax gap, although considerably smaller, was found to have effects of an audit. Audit planning might be considered as guidance for fiscal policies to lower the tax gap.